Effect of Pravastatin on eNOS and PECAM-1 Expression in the Placenta of Pre-Eclampsia Rat (Rattus norvegicus) Model - Bambang Rahardjo; Kunawati Tungga Dewi; Anita Dwi Rahmawati; Fauqo Wildatil Jannah; Mukhamad Nooryanto; Anin Indriani (Asian Journal of Health Research, 2022)
Introduction: Preeclampsia has two stages: improper placental and maternal circulation. Abnormal trophoblast invasion causes uteroplacental ischemia and hypoxia. Ischemia in the placenta produces endothelial cell dysfunction, which is defined by a change in endothelial cell activity to a reduced ability to vasodilate (decreased eNOS) and prothrombotic conditions (decreased PECAM-1). Reduced maternal eNOS activity and PECAM-1 can cause preeclampsia. Pravastatin is the statin class's most hydrophilic medication, and it limits placental transfer. Pravastatin can reduce endothelial dysfunction by targeting pleiotropic effects in pregnancy. The aim was to show the effects of pravastatin on the eNOS and PECAM-1 expression in the placenta of preeclampsia rat model. Materials and Methods: This is a true experimental study with only a post-test and a control group design. The sample was biological material in the form of placental tissue from a pravastatin-treated preeclampsia rat model (using L-NAME exposure). This research was divided into five groups, each with five samples. The parameters studied were eNOS and PECAM-1 expression. Results: The Shapiro-Wilk test result was significant (p>0.05). Annova tests on eNOS (p=0.000) and PECAM-1 expression (p=0.000) confirmed the hypothesis. The Tukey test showed significant differences in eNOS (sig. 0.001) and PECAM-1 (sig. 0.000) expression between normal and preeclampsia rats. Positive controls and treatment groups P1, P2, and P3 all showed significant changes in eNOS and PECAM-1 expression. Pravastatin dose considerably increased eNOS (p=0.015; r=0.536) and PECAM-1 (p=0.000; r=0.734) expression.. Conclusion: Pravastatin has been shown to increase eNOS and PECAM-1 expression in the placenta of preeclampsia rat model.